The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/srep16514
|View full text |Cite
|
Sign up to set email alerts
|

The Biarzo case in northern Italy: is the temporal dynamic of swine mitochondrial DNA lineages in Europe related to domestication?

Abstract: Genetically-based reconstructions of the history of pig domestication in Europe are based on two major pillars: 1) the temporal changes of mitochondrial DNA lineages are related to domestication; 2) Near Eastern haplotypes which appeared and then disappeared in some sites across Europe are genetic markers of the first Near Eastern domestic pigs. We typed a small but informative fragment of the mitochondrial DNA in 23 Sus scrofa samples from a site in north eastern Italy (Biarzo shelter) which provides a contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
(67 reference statements)
2
10
0
Order By: Relevance
“…This could be either because Y1 individuals were already there but never found before or humans exploiting this particular strain at least during the Bronze Age brought them to the islands. The first scenario is consistent with natural dispersion from other Italian areas (such as it is the case for Biarzo in Northern Italy, where pigs' remains belong to the Y2 haplotype; Vai et al, 2015). However, unlike the Y2 haplotype, which occurs in several pre-Neolithic European contexts (Evin et al, 2015, Vai et al, 2015 and in modern feral pigs from Corsica (Larson et al, 2007), the Y1 haplotype was never found in neither Mesolithic or modern European wild boar.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…This could be either because Y1 individuals were already there but never found before or humans exploiting this particular strain at least during the Bronze Age brought them to the islands. The first scenario is consistent with natural dispersion from other Italian areas (such as it is the case for Biarzo in Northern Italy, where pigs' remains belong to the Y2 haplotype; Vai et al, 2015). However, unlike the Y2 haplotype, which occurs in several pre-Neolithic European contexts (Evin et al, 2015, Vai et al, 2015 and in modern feral pigs from Corsica (Larson et al, 2007), the Y1 haplotype was never found in neither Mesolithic or modern European wild boar.…”
Section: Discussionsupporting
confidence: 61%
“…The endemic Italian clade has been previously found only in ancient Italian and Croatian specimens (Larson et al, 2007, Vai et al, 2015. Currently, the E2 clade is observed only in Central/Southern Italian wild boar and Sardinian feral populations, but never in domestic pigs (Scandura et al, 2008;Alexandri et al, 2012;Vilac¸a et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MtDNA turnover has been studied in the context of pig domestication, which is important to understand how modern human society was shaped by agricultural practice [ 59 61 ]. The present paper focuses on the distribution of mtDNA haplotypes amongst commercial pigs that were introduced to Australia.…”
Section: Discussionmentioning
confidence: 99%